Reflecting Upon Religion - Drees, Willem B. (Zygon, 2010)
Abstract. The new editor of Zygon considers the task of “yoking religion and science” not as the combination of two similar entities. Rather, their categorical difference makes reflection on their interplay worthwhile. One thereby confronts the understanding of religion, the multiple facets of religion, the diversity of religious traditions, and disagreements within religious communities. Although concern about secularization might stimulate an apologetic attitude, the author favors a critical and more skeptical attitude, countering superstition and the abuse of people. By being academic rather than apologetic we engage in the best apology for meaningful religion, if any.